PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN ANIMASI BERBASIS KINEMASTER UNTUK MENINGKATKAN EFEKTIVITAS PADA MATA PELAJARAN IPA SISWA KELAS IV SDN KEDALEMAN IV - Nurdiana Siti Alifa; Syadeli Hanafi; Lukman Nulhakim (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Online learning during the pandemic needs animated videos as learning media in science subjects at the fourth grade of elementary school. This research aimed to develop kinemaster based animation learning videos in science subjects using the ADDIE development model (analyze, design, development, implementation, and evaluation). The stages to be carried out included (a) analyzing the knowledge or competence of the target, the characteristics of the target, and the equipment that supports the use of the media, (b) designing the transferred information from the analysis phase into the form of a document aiming of making a learning video, (c) developing learning videos; the core of this activity was taking pictures or animated motion videos with an internet connection, in which the video development was carried out by using several applications, namely the kinemaster and the tubemate application. The implementation phase included implementing learning videos for fourth-grade elementary school students. Finally, the evaluation stage included the assessment of the learning media in the form of a questionnaire. The results of this development research were the animated learning videos for science learning to assist students in increasing their understanding of material concepts. The validation results from material experts showed an average of 94.3% on material, and the learning aspects with qualitative criteria were very feasible. Then, the result from media experts got an average of 87% with very decent qualitative criteria. At the same time, the students’ responses obtained an average of 97%, with very good criteria. Thus, this learning video facilitated the learning process from home so that students easily understood the concepts of science subjects on the material of force and motion of objects.